Changes in selected hematological parameters in patients with type 1 and type 2 diabetes: a systematic review and meta-analysis - Bambo, Getachew Mesfin; Asmelash, Daniel; Alemayehu, Ermiyas; Gedefie, Alemu; Duguma, Tadesse; Kebede, Samuel Sahile (Frontiers in Medicine, 2024)
Background Diabetes mellitus is a chronic metabolic disorder that causes hyperglycemia and various life-threatening health problems. Although hematological parameters play a significant role in the progression and pathogenesis of diabetes, many studies have explored contradictory findings. Therefore, this evidence-based study aimed to determine the pooled mean difference of white blood cell and red blood cell parameters in diabetic patients in order to investigate hematological dysfunctions in type 1 and type 2 diabetes mellitus. Methods Articles were extensively searched in bibliographic databases (PubMed, Cochrane library, Scopus, Web of Science, PsycINFO, Embase, online archives and university repositories) using appropriate entry terms. For studies meeting the eligibility criteria, the first author’s name, year of publication, study design and area, type of diabetes mellitus, sample size, and mean and standard deviation of hematological parameters were extracted using Microsoft Excel and exported to Stata 11 for meta-analysis. The pooled standardized mean difference (SMD) was determined using the random effects model, and heterogeneity was quantified using Higgins’ I2 statistics. Egger’s test and funnel plot were performed to measure bias. Furthermore, a sensitivity analysis was performed to determine the small study effect. Results Initially 39, 222 articles were identified. After screening of the entire methodology, 22 articles with 14,041 study participants (6,146 T2DM, 416 T1DM patients and 7,479 healthy controls) were included in this study. The pooled SMD in TLC (109/L) was 0.66 and −0.21, in T2DM and T1DM, respectively. Differences in absolute differential WBC counts for neutrophils, eosinophils, basophils, lymphocytes and monocytes in T2DM were 0.84, −1.59, 3.20, 0.36 and 0.26, respectively. The differences in relative differential counts (%) in T2DM were as follows: neutrophils: 1.31, eosinophils: −0.99, basophils: 0.34, lymphocytes: −0.19 and monocyte: −0.64. The SMD of differential counts of WBC (109/L) parameters; neutrophils, lymphocytes, monocytes and basophils in T1DM were −0.10, −0.69, 0.19, and −0.32, respectively. The pooled SMD in RBC parameters in T2DM were as follows: RBC: −0.57 (106/μL), Hb: −0.73 g/dL and HCT: −1.22%, Where as in T1DM RBC, Hb and HCT were −1.23 (106/μL), −0.80 g/dL and −0.29%, respectively. Conclusion Patients with T2DM had significantly increased TLC counts, absolute neutrophil, basophil, lymphocyte, monocyte counts and relative counts of neutrophils and basophils in comparison to controls. On the contrary, the absolute eosinophil count and relative lymphocyte, eosinophil and monocyte counts were decreased. In T1DM, WBC parameters were significantly decreased except monocytes. RBC parameters were found to be significantly decreased in T2DM patients. In T1DM, Hb and HCT were significantly decreased. However, there is no significant difference in RBC as compared with non-diabetic controls. The findings indicated a significant alteration of WBC and RBC parameters in both diabetic patients suggesting the considerable metabolic effect of diabetes on hematologic parameters. Systematic review registration https://www.crd.york.ac.uk/prospero/export_details_pdf.php, identifier [CRD42023413486].